Children’s Empathy Responses and their Understanding of Mother’s Emotions - Tully, Erin C. (2014)
This study investigated children’s empathic responses to their mother’s distress to provide insight about child factors that contribute to parental socialization of emotions. Four- to six-year-old children (N=82) observed their mother’s sadness and anger during a simulated emotional phone conversation. Children’s facial negative affect was rated and their heart rate variability was recorded during the conversation, and their emotion understanding of the conversation was measured through their use of negative emotion words and perspective-taking themes (i.e., discussing the causes or resolution of mother’s emotions) in narrative accounts of the conversation. There were positive quadratic relationships between HRV and ratings of facial affect, narrative references to mother’s negative emotions, and perspective-taking themes. High and low HRV were associated with high facial negative affect, suggesting well-regulated sympathy and poorly regulated personal distress empathic responses, respectively. Moderate HRV was associated with low facial negative affect, suggesting minimal empathic engagement. High and low HRV were associated with the highest probabilities of both emotion understanding indicators, suggesting both sympathy and personal distress responses to mother’s distress facilitate understanding of mother’s emotions. Personal distress may motivate attempts to understand mother’s emotions as a self-soothing strategy, whereas sympathy-related attempts to understand may be motivated by altruism.